Effects of Nasal Topical Corticosteroids on Nasal Secretory Immunoglobulin A in Allergic Rhinitis Patients - Kocaoz, Deniz; Ocak, Emre; Sefa Uyar, Muhammed; Mirici, Emre; Bayrak, Sevinc; Dagli, Elif; Acar, Aydin (ENT Updates, 2024)
Background: Recently, there has been interest in the immunoregulatory and preventative effects of immunoglobulin A (IgA) in individuals with allergic rhinitis (AR). Topical corticosteroids are one of the main treatment options for AR. The purpose of this study was to investigate the secretory IgA (sIgA) levels in the nasal fuid of healthy people and people who had received intranasal beclomethasone dipropionate (BD) and triamcinolone acetonide (TA) treatment. Methods: There were 29 newly diagnosed AR patients and 29 healthy control individuals in the study. Group 1 (n=13) treated with BD and group 2 (n=16) treated with TA were included. Blood samples were collected to measure IgE levels. Nasal secretions were collected through nasal packing and evaluated by enzyme-linked immunosorbent assay. Results: The mean nasal fuid sIgA level was 573.7±192.2 μg/mL in group 1, 564.8±270.8 μg/mL in group 2, and 559.7±241.9 μg/mL in the control group. The difference in baseline sIgA levels between groups was not statistically signifcant. After 1 month of nasal steroid treatment, sIgA levels in groups 1 and 2 increased signifcantly. Conclusion: It was found that adult AR patients who were being treated with 2 types of intranasal corticosteroids (BD and TA) have signifcantly higher levels of sIgA in their nasal secretions.